Performance of oilseeds in India - a temporal analysis: PERFORMANCE OF OILSEEDS IN INDIA - A TEMPORAL ANALYSIS - I KRISHNA TEJA,; S V RAMANA RAO,; D VISHNU SANKAR RAO,; B RAVINDRA REDDY, (Journal of Oilseeds Research, 2017)
The present paper explores the performance of total oilseeds in India, using times series data, collected from 1949-50 to 2014-15. Nine annual oilseeds, which include seven edible oilseeds, viz., groundnut, rapeseed-mustard, soybean, sunflower, sesame, safflower and niger along with two non-edible crops, viz., castor and linseed are grown in the country, constitutes total oilseeds in the study. The total period from 1949-50 to 2014-15 was divided into four sub-periods i.e. period I, II, III and IV. An attempt was made to analyze the trends, Compound Annual Growth Rate (CAGR), decomposition analysis, instability analysis in the area, production, yield of total oilseeds. After analysis of the performance of oilseeds, it was concluded that there was a noteworthy performance in yield aspect of total oilseeds at the national level. Though there was an upward and significant growth in terms of the area, production and yield of total oilseeds over the study period, it was sluggish. There exists a gap between domestic demand and supply of oilseeds, which obligates us to import edible oils. The government has to implicate technological breakthroughs and enhance the productivity of oilseeds to offset the gap between production and consumption of oilseeds.